77.0k views
3 votes
Hey! If you can help here it is!

Hey! If you can help here it is!-example-1
User Charlee
by
5.4k points

1 Answer

4 votes

Answer:


x=3,x=-1

Explanation:

Start with:


x(x-1)-3(x-3)+3(x-2)=x+6

Distribute the values on the outside of each of the parentheses.


x^2-x-3x+9+3x-6=x+6

Combine like terms.


x^2-x+3=x+6

Subtract
6 from both sides of the equation.


x^2-x-3=x

Subtract
x from both sides of the equation.


x^2-2x-3=0

Now, we need to use our quadratic equation formula:


ax^2+bx+c=0


x= (-b+/-√(b^2-4ac))/(2a)

Identify your values.


a=1\\b=-2\\c=-3

Substitute.

(Solve positive)


x= (-(-2)+√((-2)^2-4(1)(-3)))/(2(1))

Solve.


x= (2+√((16))/(2)

Find the square root of
16.


x=(2+4)/(2)

Add.


x=(6)/(2)

Simplify.


x=3

~

(Solve negative)


x= (-(-2)-√((-2)^2-4(1)(-3)))/(2(1))

Solve.


x= (2-√((16))/(2)

Find the square root of
16.


x=(2-4)/(2)

Subtract.


x=(-2)/(2)

Simplify.


x=-1

User Gokhan Demirhan
by
5.4k points